2017
DOI: 10.1177/1035304617690095
|View full text |Cite
|
Sign up to set email alerts
|

The implications of Australian women’s precarious employment for the later pension age

Abstract: The increase in pension eligibility ages in Australia, as elsewhere, throws into relief the consequences of gender inequality in employment. Because of career histories in lower paid and more insecure employment, a higher percentage of women than men are dependent on the age pension rather than on superannuation or savings and investments, and so will be disproportionately affected by deferred access. Yet, fewer women than men hold the types of ‘good jobs’ that will sustain them into an older age. Women are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Participants in this study had primarily worked in health care, hospitality and retail prior to entering the sex industry. This pattern reflects broader gendered employment patterns in Australia where work is highly segregated and women are disproportionately employed in these sectors (Sheen, 2017: 5).…”
Section: Career Metaphorsmentioning
confidence: 82%
“…Participants in this study had primarily worked in health care, hospitality and retail prior to entering the sex industry. This pattern reflects broader gendered employment patterns in Australia where work is highly segregated and women are disproportionately employed in these sectors (Sheen, 2017: 5).…”
Section: Career Metaphorsmentioning
confidence: 82%
“…The End of the Retirement "Age": How the New World of Work Is Transforming the Old World… DOI: http://dx.doi.org/10.5772/intechopen.92273 control over the work process itself causes stress and alienation reducing potential for continuity for the long term as many studies have shown [29][30][31][32]. It may be the case that there is overall a greater proportion of older people in the workforce now but this does not mean that there will be a strong capacity for ongoing employment well into later life.…”
Section: The Loss Of Secure Jobs and Growing Inequalitymentioning
confidence: 99%
“…Compared with single fathers, single mothers in Australia are more likely to be caring for children under five, who require the most intensive and time‐consuming care (ABS : 2; Bradbury ). They are also more likely to be precariously employed, in roles that offer less flexibility, fewer leave entitlements and less security of tenure (Huntley ; Sheen ). In this context, it seems likely that the single mothers in the sample were particularly likely to have trouble finding and maintaining paid work.…”
Section: Interpretation Of the Datamentioning
confidence: 99%